Fungsi lanskap linguistik dalam menciptakan kesehatan lingkungan di Rumah Sakit Umum Daerah Provinsi Papua Barat: Kajian ekolinguistik - Yani, Ahmad; Hussen, Muhammad; Igga, Imoifa (Cassowary, 2026)
ABSTRACT : This study aims to identify the availability of linguistic landscapes in the Provincial General Hospital of West Papua Province in Manokwari and to describe the functions of the linguistic landscapes in promoting environmental health. This study was a descriptive qualitative study using a documentation method which tried to potrait the situation in the place. Data were collected using purposive sampling technique and analyzed using descriptive method. The use of purposive sampling technique was to ensure that the data contained significant amount of verbal information and that they addressed environmental health issues. The results showed that there were 14 linguistic landscapes in the hospital, comprising of 6 prohibition landscapes, 5 information landscapes, and 2 procedure landscapes